Mechanical modeling and characteristic study for the adhesive contact of elastic layered media. (31st October 2017) - Zhang, Yuyan; Wang, Xiaoli; Tu, Qiaoan; Sun, Jianjun; Ma, Chenbo
Abstract: This paper investigates the adhesive contact between a smooth rigid sphere and a smooth elastic layered medium with different layer thicknesses, layer-to-substrate elastic modulus ratios and adhesion energy ratios. A numerical model is established by combining elastic responses of the contact system and an equation of equivalent adhesive contact pressure which is derived based on the Hamaker summation method and the Lennard–Jones intermolecular potential law. Simulation results for hard layer cases demonstrate that variation trends of the pull-off force with the layer thickness and elastic modulus ratio are complex. On one hand, when the elastic modulus ratio increases, the pull-off force decreases at smaller layer thicknesses, decreases at first and then increases at middle layer thicknesses, while increases monotonously at larger layer thicknesses. On the other hand, the pull-off force decreases at first and then increases with the increase in the layer thickness. Furthermore, a critical layer thickness above which the introduction of hard layer cannot reduce adhesion and an optimum layer thickness under which the pull-off force reaches a minimum are found. Both the critical and optimum layer thicknesses become larger with an increase in the Tabor parameter, while they tend to decrease with the increase in the elastic modulus ratio. In addition, the pull-off force increases sublinearly with the adhesion energy ratio if the layer thickness and elastic modulus ratio are fixed.